Land Tenure Reform in Sub-Saharan Africa : Interventions in Benin, Ethiopia, Rwanda, and Zimbabwe. - Lawry, Steven (Routledge Focus on Environment and Sustainability Series., 2023)
"This book examines the impacts of land tenure reform interventions implemented in Benin, Ethiopia, Rwanda, and Zimbabwe. Since 2000, many African countries have introduced programs aimed at providing smallholder farmers with low-cost certificates for land held under customary tenure. Yet there are many contending views and debates on the impact of these land policies and this book reveals how tenure security, agricultural productivity and social inclusion were affected by the interventions. It analyses the results of carefully selected, authoritative studies on interventions in Benin, Ethiopia, Rwanda, and Zimbabwe and applies a realist synthesis methodology to explore the socio-political and economic contexts. Drawing on these results, the book argues that inadequate attention paid to the core characteristics of rural social systems obscures the benefits of customary tenure while overlooking the scope for reforms to reduce the gaps in social status among members of customary communities. The book will be of great interest to students and scholars of land management and use, land and property law, tenure security, agrarian studies, political economy and sustainable development. It will also appeal to development professionals and policymakers involved in land governance and land policy in Africa"-- Provided by publisher.